Evolution of complex structures: minicollagens shape the cnidarian nematocyst - David, Charles N.; Özbek, Suat; Adamczyk, Patrizia; Holstein, Thomas W. (Trends in genetics, 2008)
The generation of biological complexity by the acquisition of novel modular units is an emerging concept in evolutionary dynamics. Here, we review the coordinate evolution of cnidarian nematocysts, secretory organelles used for capture of prey, and of minicollagens, proteins constituting the nematocyst capsule. Within the Cnidaria there is an increase in nematocyst complexity from Anthozoa to Medusozoa and a parallel increase in the number and complexity of minicollagen proteins. This complexity is primarily manifest in a diversification of N- and C-terminal cysteine-rich domains (CRDs) involved in minicollagen polymerization. We hypothesize that novel CRD motifs alter minicollagen networks, leading to novel capsule structures and nematocyst types.